ON THE SPECIFICS OF TEACHING, SCHOOLS AND INTELLECTUAL CENTERS OF PALESTINE OF LATE ANTIQUITY - Zhanna M. Sukhova; Irina Yu. Vashcheva (Sovremennye Issledovaniâ Socialʹnyh Problem)
Background. Late Antiquity is a specific and unique historical period that has been actively studied in recent decades, with certain topics that still require detailed researches. The educational system of this period had many transformations and remained an important part of the cultural and spiritual development of an individual. The cities of Palestine took a special place among the educational and intellectual centers of the Roman and Byzantine empires, where classical, Jewish, and Christian traditions intertwined.